2021
DOI: 10.1039/d1nr00385b
|View full text |Cite
|
Sign up to set email alerts
|

Switching on near-infrared light in lanthanide-doped CsPbCl3 perovskite nanocrystals

Abstract: The accessible emission spectral range of lead halide perovskite (LHP) CsPbX3 (X = Cl, Br, I) nanocrystals (NCs) has remained so far limited to wavelengths below 1 μm, corresponding to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 55 publications
0
31
1
Order By: Relevance
“…Noteworthy co-doped systems have also been reported, including CsPbCl 1.5 Br 1.5 :Yb 3+ ,Ce 3+ NPs which utilize quantum cutting to improve the photoelectric conversion efficiency of commercial silicon solar cells from 18.1% to 21.5%, 15 Yb 3+ -Er 3+ codoped CsPb(Cl 1−x Br x ) 3 NPs that use host sensitization to boost the Er 3+ emission at 1.5 μm for applications in telecommunications, 20 and Mn 2+ mediated energy transfer that switches on intense NIR emission for Nd 3+ , Ho 3+ , and Er 3+ in CsPbCl 3 :Mn 2+ , Ln 3+ [Ln = Nd, Ho, and Er] NPs. 21 An alternate protocol to the direct synthetic routes discussed for doping Ln 3+ in perovskite NPs can be envisioned via a post-synthetic procedure. The post-synthetic introduction of Ln 3+ in traditional II-VI semiconductor NPs and the investigation of their corresponding photophysical properties has been explored by us in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy co-doped systems have also been reported, including CsPbCl 1.5 Br 1.5 :Yb 3+ ,Ce 3+ NPs which utilize quantum cutting to improve the photoelectric conversion efficiency of commercial silicon solar cells from 18.1% to 21.5%, 15 Yb 3+ -Er 3+ codoped CsPb(Cl 1−x Br x ) 3 NPs that use host sensitization to boost the Er 3+ emission at 1.5 μm for applications in telecommunications, 20 and Mn 2+ mediated energy transfer that switches on intense NIR emission for Nd 3+ , Ho 3+ , and Er 3+ in CsPbCl 3 :Mn 2+ , Ln 3+ [Ln = Nd, Ho, and Er] NPs. 21 An alternate protocol to the direct synthetic routes discussed for doping Ln 3+ in perovskite NPs can be envisioned via a post-synthetic procedure. The post-synthetic introduction of Ln 3+ in traditional II-VI semiconductor NPs and the investigation of their corresponding photophysical properties has been explored by us in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy co-doped systems have also been reported, including CsPbCl 1.5 Br 1.5 :Yb 3+ ,Ce 3+ NPs which utilize quantum cutting to improve the photoelectric conversion efficiency of commercial silicon solar cells from 18.1% to 21.5%, 15 Yb 3+ –Er 3+ codoped CsPb(Cl 1− x Br x ) 3 NPs that use host sensitization to boost the Er 3+ emission at 1.5 μm for applications in telecommunications, 20 and Mn 2+ mediated energy transfer that switches on intense NIR emission for Nd 3+ , Ho 3+ , and Er 3+ in CsPbCl 3 :Mn 2+ , Ln 3+ [Ln = Nd, Ho, and Er] NPs. 21…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 5 , 25 − 29 Various reports have shown that in lead halide perovskites a downshifted luminescence in the visible and infrared spectral range can be achieved through doping with divalent cations (for instance, Cd 2+ , Mn 2+ ), 30 , 31 trivalent cations (Ln 3+ ), 27 , 32 , 33 or a combination thereof. 28 Yet, the toxicity and stability issues of lead-based perovskites are a strong drive toward alternative metal halides, 34 37 and several Pb-free double perovskites (e.g., Cs 2 AgInCl 6 , 38 40 Cs 2 AgBiX 6 (X = Cl, Br), 39 , 41 and Cs 3 Bi 2 Br 9 39 ) have been synthesized and tested as hosts. Furthermore, most of these materials absorb only in the blue-visible range (<500 nm).…”
mentioning
confidence: 99%
“…In this work, we successfully synthesized partially Mn-doped CsPbBr 3 by hot injection technique. 35–42 Then we demonstrate the Mn:CsPbMnBr 3 PQDs with a Mn substitution ratio up to 38%. The introduction of Mn 2+ significantly increased the formation energy of Pb, Br, and Cs vacancies.…”
Section: Introductionmentioning
confidence: 86%